Do graduate courses in a HyFlex mode foster emotional, cognitive and behavioral engagement? A consideration (Journal of Applied Learning and Teaching, 2024)
The global pandemic accelerated the adoption of online, blended, and Hybrid Flexible (HyFlex) teaching and learning modalities. The long-term impacts of these changes are still being assessed, but most research to date has focused on undergraduate students in an online setting. In contrast, this study reviews recent research pertaining to HyFlex engagement strategies used by academic staff and personnel with teaching responsibilities at the graduate level and considers how HyFlex courses, the combination of face-to-face instruction and online activities, may foster equivalent learning outcomes, as well as comparable emotional, cognitive, and behavioral engagement. Using a critical reflective approach, the study finds that graduate-level courses taught in a HyFlex mode can offer equivalent learning outcomes, but such outcomes require academic staff development and purposefully designed activities that directly promote emotional, cognitive, and behavioral engagement. Several practical strategies and suggestions to improve engagement are offered.